Pulmoner nodül rezeksiyonu yapılan olgularda klinik radyolojik bulguların malign histopatolojik tanılar ile korelasyonu - OLGUN YILDIZELİ, ŞEHNAZ; KOCAKAYA, DERYA; ERMERAK, NEZİH ONUR; BOZKURTLAR, EMİNE; ERYÜKSEL, SEMİHA EMEL; ÇİMŞİT, NURİ ÇAGATAY; YILDIZELİ, BEDRETTİN; KARAKURT, SAİT (My University, 2023)
Pulmonary nodules are common (nc(dental f(nd(ng on thorac(c computed tomography (CT) and st(ll a problem (n da(ly pulmonary pract(ce. Because of the w(dely usage of CT scans an (ncreased number of pat(ents follow up w(th th(s d(agnose. Nodules may or(g(nated secondary to ben(gn d(seases but pr(mary concern (s mal(gnanc(es wh(ch (s (mportant for early d(agnos(s and curat(ve opt(ons. On the other hand (t (s not cost-effect(ve follow(ng up the ben(gn les(ons w(th an add(t(onal cumulat(ve rad(at(on dose espec(ally (n prolonged durat(on. Many pred(ct(on models were proposed to evaluate the potency of mal(gnancy us(ng cl(n(cal and rad(olog(cal f(nd(ngs Mayo cl(n(c (1), Veterans Assoc(at(on (2), Brock Un(vers(ty (3) and lastly Herder model (4) mostly used models for r(sk strat(f(cat(on. Herder r(sk model evaluates also Flour(ne– flourodeoxyglucose (FDG) uptake (n pos(tron em(ss(on tomography-computed tomography (PET-CT). Comparat(ve study of these models showed non-super(or(ty to each other, added value of PET-CT (s unden(able for larger nodules but not clear for small nodules (< 8mm) (5). Mult(d(sc(pl(nary follow up, careful observat(on and d(agnost(c test(ng are st(ll h(ghly recommended espec(ally for (ndeterm(ne nodules